Exploring resilience: a Bayesian study of psychological and financial factors across gender - Arturo García-Santillán; Milka Elena Escalera-Chávez; Josefina C. Santana (Cogent Economics & Finance)
The study aims to demonstrate gender differences in financial health indicators, assessed through perceptions, lived experiences, and actions to deal with financial crises. The scale used is a composite instrument that includes the eight financial health indicators from BBVA and the Center for Financial Services Innovation (CFSI), together with a scale designed to measure lived experiences and actions to manage financial crises. The sample consisted of 951 participants, 394 (41.4%) men, 504 (53.0%) women, and 53 (5.6%) LGBTQ+. Bayesian analysis indicates that perceptions, lived experiences, and actions in managing economic crises do not differ significantly between genders. The study suggests no significant differences in financial resilience between men, women, and LGBTQ+ people. Actions to cope with economic crises also indicate that resilience does not vary significantly by gender. Despite the absence of gender differences in financial perceptions and experiences, it is inferred that participants possess an acceptable level of financial knowledge, which helps them manage unforeseen expenses and reduce dependence on loans. Financial education is a key factor in strengthening resilience and promoting financial inclusion, which is essential, especially in diverse socioeconomic contexts. The findings suggest that financial inclusion may improve household resilience, particularly in rural areas.